Treatment outcome of 301 aplastic anemia patients in China: a 10-year follow-up and real-world data from single institute experience. Issue 1 (1st January 2021) - Zhang, Xiao-tian; Wang, Xue; Cao, Jiang; Chen, Wei; Qi, Kun-ming; Qi, Na; Liang, Fei; Dong, Xue-yan; Tang, Guo-feng; Li, De-peng; Sang, Wei; Li, Zhen-yu; et al.
ABSTRACT: Objective: This study was carried out to explore clinical treatment and prognosis of patients with AA with different economic status. Methods: We retrospectively analyzed the clinical outcome of 301 patients with AA in our center from April 2008 to November 2017. Results: Treatments included anti-thymocyte globulin (ATG) or anti-lymphocyte globulin (ALG) combined with cyclosporineA (CsA) (9%), allogeneic hematopoietic stem cell transplantation (allo-HSCT) (7%), CsA combined with androgen or CsA alone (hereinafter referred to as CsA group) (77%), no specific therapy (7%). The 5-year overall survival (OS) was higher in patients with non-severe AA (94.6%) compared with those with severe AA (SAA) (66.6%, P <.001), very severe AA (VSAA) (41.3%, P <.001). The 5-year OS was 76.5% in patients with SAA/VSAA treated with ATG/ALG combined with CsA, 75% in allo-HSCT group(P =.936), 63.6% in CsA group ( P =.557), which was significantly higher than no specific therapy group (21.8%, P =.002). For those who responded to CsA, the duration of CsA (median follow-up time: 27 months, 1–101 months) was positively correlated with progression-free survival (r=0.603, P <.001). Multivariate analysis revealed that 36–65 years of age, SAA/VSAA, and no specific therapy were independent risk factors for inferior survival. Conclusion: The treatment of elderly patients with AA still faces challenges. CsA is benefit to the survival of SAA/VSAA patients. AA patients, who responded to initialy CsA treatment, may benefit from prolonged CsA treatment. In view of the side effects of CsA, the timing of withdrawal is worth further exploration.